Guépard-gazelle : entre prédation et care, construction de l’ethos discursif de femmes chasseresses - Guillonne Balaguer (Glad!)
Based on an ethnographic sociolinguistic study of women's hunting, this article looks at the construction of the discursive ethos of women hunters, between care and predation. Starting from a feminist theoretical context that links women and animals to the same male oppression (the figure of the prey-woman), I examine the strategies of adaptation and avoidance in the words of the female hunters who took part in my study, and then the way in which they construct an ethos of empowering predators, in a positive axiology of animality, while refusing the status of prey-woman. I then look at their assumption of feminine assignments to care, between concern for animals and the activation of stereotypes of the feminine, particularly around motherhood. Finally, I analyse examples of anthropomorphisation and animalisation, which highlight a disturbance at the inter-species boundary. In this way, I attempt to show the complexity of a plural ethos, in tension between care and kill, in which female hunters assert themselves, overturning essentialist paradigms linking woman and prey, hunting and masculinity, while using gender assignments to construct their discursive identity.